Daily monetary policy rules and the ECB's medium-term orientation - Jens Klose (Philipps-University Marburg, School of Business and Economics, 2021)
This article develops the first granular database on daily real-time inflation rates and output. Four different European forecast sources and three computation methods are applied to calculate those daily data. These are used in two types of monetary policy rules, for three different interest rates as the dependent variable. The results indicate that the main source of differences in the forecast horizons and response coefficients is not the data sources or the computation method but, rather, the monetary policy rule applied and the interest rate used. That is, the results differ if unconventional monetary policies are considered. Moreover, the results tend to be time-varying; that is, sudden shifts in the optimal forecast horizon can be identified, leading to substantially altered policy rules.
Keywords: E52; E58; 330; Monetary policy rules; ECB; medium-term orientation